1. In Vitro and In Vivo Activity of Sulfur-Containing Linear Bisphosphonates against Apicomplexan Parasites - Szajnman, Sergio Hernan (2016)
We tested a series of sulfur-containing linear bisphosphonates against Toxoplasma gondii, the etiologic agent of toxoplasmosis. The most potent compound (compound 22; 1-[(n-decylsulfonyl)ethyl]-1,1-bisphosphonic acid) is a sulfonecontaining compound, which had a 50% effective concentration (EC50) of 0.11 ± 0.02 μM against intracellular tachyzoites. The compound showed low toxicity when tested in tissue culture with a selectivity index of >2,000. Compound 22 also showed high activity in vivo in a toxoplasmosis mouse model. The compound inhibited the Toxoplasma farnesyl diphosphate synthase (TgFPPS), but the concentration needed to inhibit 50% of the enzymatic activity (IC50) was higher than the concentration that inhibited 50% of growth. We tested compound 22 against two other apicomplexan parasites, Plasmodium falciparum (EC50 of 0.6 ± 0.01 μM), the agent of malaria, and Cryptosporidium parvum (EC50 of ∼65 μM), the agent of cryptosporidiosis. Our results suggest that compound 22 is an excellent novel compound that could lead to the development of potent agents against apicomplexan parasites.